Cerita â€œHibatâ€ Karangan R.H. Moehamad Meosa sebagai Embrio Cerita Pendek Sunda dalam Wacana Kolonialisme Abad ke-19 - Darpan, Darpan (LOKABASA, 2019)
The research is based on the assumption that literary works written in the second half of the 19th century were the result of the efforts of the Dutch colonial government to incorporate the ideology of colonialism in culture field, and tried to instill modern ideas from the West through literacy activities. Some of these texts are stories written in short prose that are realistic. The story of "Hibat" is one of them. Based on the narrative characteristics, it can be concluded that the story can be regarded as a Sundanese short story embryo in its modern concept. The analysis of the story "Hibat" was carried out with the aim of finding the form of writing configuration and its narrative characteristics so that the elements of the story were found to be different from the traditions of the previous story writing. Through descriptive methods and structural analysis techniques, it is known that the story "Hibat" is unique and different when compared to the tradition of story writing in more traditional Sundanese. The story shows new features including its configuration written in short prose, leaving the tradition of old story writing that indulges in fantasy, myths, and irrationality, and written with the awareness of wanting to portray everyday life in its environment. The implications of this study must be corrective efforts in the history of Sundanese literature, which considered the birth of Sundanese short stories beginning with the emergence of the Parahiangan magazine (1929-1942) and the publication of Dogdog PangrÃ©wong by G.S. in 1930.AbstrakPenelitian ini didasarkan pada asumsi bahwa karya sastra yang ditulis pada paruh kedua abad ke-19 adalah hasil dari upaya pemerintah kolonial Belanda untuk memasukkan ideologi kolonialisme dalam bidang budaya, dan mencoba menanamkan ide-ide modern dari Barat melalui kegiatan literasi. Beberapa dari teks-teks tersebut adalah cerita yang ditulis dalam prosa pendek yang realistik. Cerita "Hibat" adalah salah satunya. Berdasarkan ciri-ciri naratifnya, dapat disimpulkan bahwa cerita â€œHibatâ€ dapat dianggap sebagai embrio cerita pendek Sunda dalam konsepnya yang modern. Analisis cerita "Hibat" dilakukan dengan tujuan menemukan bentuk konfigurasi penulisan dan ciri-ciri naratifnya sehingga ditemukan unsur-unsur cerita yang berbeda dari tradisi penulisan cerita sebelumnya. Melalui metode deskriptif dan teknik analisis struktural, diketahui bahwa cerita "Hibat" mengandung keunikan dan berbeda jika dibandingkan dengan tradisi penulisan cerita dalam bahasa Sunda yang lebih tradisional. Cerita ini menunjukkan unsur-unsur baru antara lain konfigurasinya ditulis dalam prosa pendek, meninggalkan tradisi penulisan cerita lama yang menonjolkan fantasi, mitos, dan irasionalitas, serta ditulis dengan kesadaran ingin menggambarkan kehidupan sehari-hari di lingkungan pengarangnya. Implikasi dari penelitian ini harus ada upaya korektif dalam sejarah sastra Sunda, yang menganggap kelahiran cerita pendek Sunda dimulai dengan munculnya majalah Parahiangan (1929-1942) dan penerbitan buku Dogdog PangrÃ©wong karangan G.S pada tahun 1930.